Effect of Benzoic Acids on Barite and Calcite Precipitation - Freeman, Sandra; Jones, Franca; Ogden, Mark; Oliveira, Allan; Richmond, William (American Chemical Society, 2006)
The effect of various benzoic acids on the precipitation of barite (BaSO4) and calcite (CaCO3) was investigated. The acids varied in the number of carboxylate groups, from dibenzoic acids (phthalic, isophthalic, and terephthalic) through to the hexabenzoic acid (mellitic acid). It was found that the stereochemistry of the dibenzoic acids was important, as was the pH of the solution (trimesic acid was used as a test case and showed that greatest inhibition was achieved with all carboxylate groups deprotonated). Interestingly, for both the calcite and barite systems, mellitic acid was found to be both a potent inhibitor and a significant crystal growth modifier. In the case of barite, the presence of mellitic acid produced nanoparticles that agglomerated. The nanoparticles were found to be 20 nm in size from X-ray diffraction (XRD) line width analysis and 20-50 nm from transmission electron microscopy (TEM). Humic acid was also tested and found to form bundled fibers of barium sulfate.